Transcriptomic evaluation of the American oyster, Crassostrea virginica, deployed during the Deepwater Horizon oil spill: Evidence of an active hydrocarbon response pathway. (September 2016) - Jenny, Matthew J.; Walton, William C.; Payton, Samantha L.; Powers, John M.; Findlay, Robert H.; O'Shields, Britton; Diggins, Kirsten; Pinkerton, Mark; Porter, Danielle; Crane, Daniel M.; Tapley, Jeffrey; Cunningham, Charles
Abstract: Estuarine organisms were impacted by the Deepwater Horizon oil spill which released ∼5 million barrels of crude oil into the Gulf of Mexico in the spring and summer of 2010. Crassostrea virginica, the American oyster, is a keystone species in these coastal estuaries and is routinely used for environmental monitoring purposes. However, very little is known about their cellular and molecular responses to hydrocarbon exposure. In response to the spill, a monitoring program was initiated by deploying hatchery-reared oysters at three sites along the Alabama and Mississippi coast (Grand Bay, MS, Fort Morgan, AL, and Orange Beach, AL). Oysters were deployed for 2-month periods at five different time points from May 2010 to May 2011. Gill and digestive gland tissues were harvested for gene expression analysis and determination of aliphatic and polycyclic aromatic hydrocarbon (PAH) concentrations. To facilitate identification of stress response genes that may be involved in the hydrocarbon response, a nearly complete transcriptome was assembled using Roche 454 and Illumina high-throughput sequencing from RNA samples obtained from the gill and digestive gland tissues of deployed oysters. This effort resulted in the assembly and annotation of 27, 227 transcripts comprised of a large assortment of stress response genes, including members of the aryl hydrocarbon receptor (AHR) pathway, Phase I and II biotransformation enzymes, antioxidant enzymes and xenobiotic transporters. From this assembly several potential biomarkers of hydrocarbon exposure were chosen for expression profiling, including the AHR, two cytochrome P450 1A genes (CYP1A-like 1 and CYP1A-like 2), Cu/Zn superoxide dismutase (CuZnSOD), glutathione S-transferase theta (GST theta) and multidrug resistance protein 3 (MRP3). Higher expression levels of GST theta and MRP3 were observed in gill tissues from all three sites during the summer to early fall 2010 deployments. Linear regression analysis indicated a statistically significant relationship between total PAH levels in digestive gland tissue samples with CYP1A-like 2, CuZnSOD, GST theta and MRP3 induction. These observations provide evidence of a potentially conserved AHR pathway in invertebrates and yield new insight into the development of novel biomarkers for use in environmental monitoring activities. Highlights: Deployed oysters were used to monitor effects of the 2010 Macondo oil spill. Next-generation sequencing was used to identify classic stress response genes. Deployed oysters expressed multiple genes associated with hydrocarbon toxicity. Expression of multiple genes significantly correlated with PAH tissue levels.